Peningkatan Kemampuan Membaca Kalimat Melalui Media Wordwall bagi Peserta Didik Disabilitas Intelektual Ringan - Revina, Rahma Novianti; Zulmiyetri, Zulmiyetri; Iswari, Mega; Taufan, Johandri (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the problems encountered by students with mild intellectual disabilities in the seventh grade at SLB Negeri 1 Kubung. The problem experienced by the students is difficulty in reading sentences consisting of three words. This research aims to improve reading skills using the wordwall media. This study uses a quantitative approach with experimental methods, single subject or Single Subject Research (SSR), and uses an A-B design which consists of Baseline (A1) and Intervention (B). The data collection technique is in the form of tests and the data collection tool is observation by recording the students' abilities. Meanwhile, the data analysis technique used is graphic visual analysis. The research results show that at the initial baseline phase (A1), conducted over three meeting sessions, the stable data result was at a percentage of 26%. Meanwhile, the intervention, carried out over nine meetings, showed that the stable data percentage was in the range of 70%. Based on the research results, it can be concluded that the Wordwall media can improve the reading ability of students with mild intellectual disabilities.